2014
DOI: 10.1039/c4sm00928b
|View full text |Cite
|
Sign up to set email alerts
|

Probing the association of triblock copolymers with supported lipid membranes using microcantilevers

Abstract: Pluronics are a class of amphiphilic triblock copolymers that are known to interact with cellular membranes in interesting ways. The solubility of these triblock copolymers in free lipid membranes can be altered with temperature, allowing the possibility of tuning their membrane insertion. However, for supported lipid membranes, the asymmetric local environment and the strong influence of the solid support can alter the solubility of these triblock copolymers in lipid membranes. Here, we probe the interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 64 publications
5
37
0
1
Order By: Relevance
“…Earlier work using lipid monolayers, unilamellar vesicles, or supported bilayers as model membrane systems has provided some physical insight into polymer-membrane association. 24,25,26,27,28,29 For example, it has been proposed that the hydrophobic PPO block favors insertion into the lipid tail region, whereas the hydrophilic PEO block may only weakly adsorb onto the lipid headgroups. 25 Small angle X-ray scattering (SAXS) experiments by Firestone et al further demonstrated that the length of the hydrophobic PPO block is a key determinant of the interaction mechanism with lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier work using lipid monolayers, unilamellar vesicles, or supported bilayers as model membrane systems has provided some physical insight into polymer-membrane association. 24,25,26,27,28,29 For example, it has been proposed that the hydrophobic PPO block favors insertion into the lipid tail region, whereas the hydrophilic PEO block may only weakly adsorb onto the lipid headgroups. 25 Small angle X-ray scattering (SAXS) experiments by Firestone et al further demonstrated that the length of the hydrophobic PPO block is a key determinant of the interaction mechanism with lipid bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 A previous study of polymer interactions with supported lipid membranes using a microcantilever compared two Pluronics with the same PPO/PEO ratio but different molecular weight, and found that higher molecular weight enhances the association with lipid membranes. 29 Recently, on the basis of an in-vitro cellular assay it was found that the protection efficacy of PPO-PEO block copolymers on cell membranes is highly affected by the polymer composition as well as the overall molecular weight. 35 In this context, the polymer structure plays a critical role in the nature of the interactions between PPO-PEO block copolymers and lipid membranes, which therefore determines the performance of polymers in both membrane stabilization and permeabilization.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained from molecular dynamics simulations 46,47 . At fixed PEO/PPO ratio, it was experimentally observed that increasing molecular weight enhanced interaction between the polymer and lipid, retarding the lipid diffusion in turn 48,49 . Conformations of the poloxamers interacting with lipid membranes have been studied by synchrotron X-ray scattering 50,51 and computational simulation 52 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, temperature can play an important role on the solubility of the polymer in the membranes. 16 Experiments generally indicate that the interactions occur in two possible scenarios: (1) adsorption of polymer to the membrane surface, which is observed in all types of Pluronics, and (2) insertion of more hydrophobic polymers into the membrane. Although these observations appear consistent among experiments, a clear understanding of the mechanisms and driving forces that facilitate Pluronic−membrane interactions at atomic level remains elusive.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To design effective nanomedicines, it is important to understand these interactions and the underlying molecular mechanisms in detail. Several experimental studies have been conducted in this context using different types of Pluronics, membrane models (monolayers, 14 bilayers, 15,16 liposomes, 9,17 and cells 18 ), and experimental methods including fluorescence microscopy, 14 X-ray scattering and differential scanning calorimetry, 15,17,19 dynamic nuclear polarization, 9 and microcantilever sensing. 16 Most of these studies indicate that the association of Pluronics with the lipid membranes depends on the length of the PPO block, hydrophilicity of the copolymer, membrane type, and membrane composition.…”
Section: ■ Introductionmentioning
confidence: 99%